New Associations or New Politics? : The Significance of Israeli-style Post-materialism - Ben-Eliezer, Uri (Hagar: Studies in Society and Culture, 2003)
Over the past decade, in Israel, public interest has developed on a variety of issues related to the individual, his/her rights, preferences, body and identity, as well as his/her environment (mainly the ecological one). These issues are at the core of various forms of protest, guided by grass-roots organizations, non-profit associations, and new social movements. According to the government registrar of non-profit associations, there are close to 30,000 such associations in Israel today, whereas in 1982, there were only 3,000. The associations differ from one another in their level of organization, objectives, strategies, style, identities, framework and relationship with the state. It is abundantly clear that they represent a new phenomenon in the Israeli landscape. The article’s main objective is first, to describe the historical and institutional circumstances that elicited this new phenomenon and determined its basic features for many years to come; second, to depict the contradictions embedded within the new phenomenon on two levels: identity politics and instrumental politics; and third, to delineate the inability of many new associations to free themselves from the state’s bear hug. All in all, the manuscript’s main thesis is that numerous obstacles still exist to Israel becoming more democratic, with a genuine civil society at its center, one that is more open to global trends, and less dependent on state authorities and the neo-liberal market.